Analysis of Social Media Perceptions During the COVID-19 Pandemic in the United Kingdom: Social Listening Study (2019-2022) - Marzieh Araghi; Arron Sahota; Maciej Czachorowski; Kevin Naicker; Natalie Bohm; Katie Phillipps; James Gaddum; Erica Jane Cook (JMIR Formative Research)
Abstract BackgroundSocial media listening can be leveraged to obtain authentic perceptions about events, their impact, guidelines, and policies. There has been to date no research that has examined the experiences of patients with COVID-19 from diagnosis to treatment using social media listening in the United Kingdom. ObjectiveThis study aimed to assess public perceptions, insights, and sentiments throughout the patient journey from diagnosis to treatment during the COVID-19 pandemic. MethodsA comprehensive search query was designed to retrieve social media data that referred to COVID-19 and treatment. The search was conducted using the social media monitoring tool, Synthesio (Ipsos). Data were retrospectively collected for the period covering September 2019 to September 2022 from Twitter (subsequently rebranded X), Facebook, Instagram, and YouTube as well as 126 public forums (including Health Unlocked, Mums Net, The Student Room, and Patient Forums UK). Available data in the United Kingdom expressed in the English language were collected and filtered, generating a final dataset consisting of 31,319 posts from an overall initial dataset of 706,634 posts. Complimentary Google trend analyses of search terms mentioning COVID-19 treatments were also performed. ResultsSocial media posts related to COVID-19 symptoms accounted for 6% of overall posts, compared to 35% of posts related to testing, 25% of posts related to diagnosis, and 32% of posts related to treatment. Overall, the trend observed from social media posts relating to COVID-19 treatment extracted in Synthesio was largely congruent with the trend of COVID-19 searches on Google, indicating a potential relationship between public discourse and social media and internet search behavior. ConclusionsThe findings from this study have the potential to inform decision-making regarding public health interventions, communication strategies, and health care policies in the United Kingdom during future public health emergencies.